Feeding Relationship between Octopus vulgaris (Cuvier, 1797) Early Life-Cycle Stages and Their Prey in the Western Iberian Upwelling System: Correlation of Reciprocal Lipid and Fatty Acid Contents - Lourenço, Sílvia; Roura, Álvaro; Fernández-Reiriz, María-José; Narciso, Luís; González, Ángel F. (Frontiers in Physiology, 2017)
Under the influence of the Western Iberian upwelling system, the Iberian Atlantic coast holds important hatcheries and recruitment areas for Octopus vulgaris. Recently identified as an octopus hatchery, the Ría de Vigo harbours an important mesozooplankton community that supports O. vulgaris paralarvae during the first days of their planktonic stage. This study represents a preliminary approach to determine the nutritional link between wild O. vulgaris hatchlings, paralarvae and their zooplankton prey in the Ría de Vigo, by analysing their lipid class content and fatty acid profiles. The results show that octopus hatchlings are richer in structural lipids as phospholipids and cholesterol, while the zooplankton is richer in reserve lipids like triacylglycerol and waxes. Zooplankton samples are also particularly rich in C18:1n9 and 22:6n3 (DHA), that seem to be successfully incorporated by O. vulgaris paralarvae thus resulting in a distinct fatty acid profile to that of the hatchlings. On the other hand, content in C20:4n6 (ARA) is maintained high through development, even though the zooplankton is apparently poorer in this essential fatty acid, confirming its importance for the development of O. vulgaris paralarvae. The content in monounsaturated fatty acids, particularly C18:1n7, and the DHA: EPA ratio are suggested as trophic markers of the diet of O. vulgaris paralarvae.